Property development in n-alkane and n-alkane eutectic phase change materials for thermal energy storage applications - Cemil Alkan; Erdinç Halis Alakara (Solar Energy Advances)
In this study, some n-alkanes (n-heptadecane: C17, n-octadecane: C18, n-nonadecane: C19, n-eicosane: C20, and n-tetracosane: C24) were used to determine their physicochemical properties to reveal the relationships between the molecular structure and properties. The materials studied were having working temperatures from 21.4 to 46.5 °C and enthalpy storage capacity from 216.2 to 268.9 J/g. Other thermophysical properties relevant to thermal energy storage, like specific heat capacity, thermal conductivity, density, and refractive index, are also investigated and formulated as properties changing with respect to molar mass and carbon number. In addition, some eutectic mixtures of the n-alkane compounds used were prepared, and the thermal energy storage properties, especially phase change temperature and enthalpy, were examined. Binary eutectic mixtures of C17-C18, C20-C17, C20-C19, and C20-C24were having phase change temperatures from 20.6 to 35.8 °C and enthalpy storage capacity from 215.1 to 265.6 °C. While preparing eutectic mixtures, the Schrader equation was used to estimate the eutectic composition points, and then the accuracy of the equation was examined. The studies were conducted based on Differential Scanning Calorimetry (DSC), which has extremely high accuracy. The ranges and dynamics of the analysis methods were chosen according to the needs of potential applications. Besides, varios compositions were investigated to determine the eutectic point experimentally. Mixing was found having a negative effect on the phase change enthalpy. This study, therefore, revealed whether eutectic mixtures have suitable enthalpy as well as phase transition temperature for the desired application area.